Strategies for retention and completion in vocational education: faculty perspectives - Yamjal, Parina; AL-Sa’di, Ahmed (Journal of Management and Business Education, 2023)
The purpose of this paper is to identify and discuss the strategies for retention and completion in vocational education. We are reporting on one New Zealand polytechnic institution’s experience in improving the retention and completion rate for a one-year diploma in business programme. A review of relevant literature pertaining to retention and completion strategies in tertiary education in general and for vocational education in particular was performed to understand the factors dominant in dropout decisions of tertiary students and to explore retention and completion strategies from a wider body of knowledge. The review focused on strategies influencing institutional and interactive factors to identify this issue. Further, a qualitative study was conducted; data was collected by conducting one-on-one interviews using open-ended questions to survey the faculty teaching on the diploma programme at a New Zealand polytechnic. The findings revealed faculty employed a range of practices for improving interaction with students, identifying at-risk students, and providing them with support, creating a collaborative learning environment, and employing a constructive feedback system to improve retention and completion in the programme. This study is expected to assist educators and tertiary institutions in prioritising retention and completion issues and adopting suitable strategies to address these issues.